An investigation of polyacrylate adsorption onto hematite - Kirwan, Luke J. (Curtin University, 2002)
For the majority of tailings substrates, flocculant adsorption proceeds through hydrogen bonding of the amide functionalities with neutral surfaces. However, flocculation of Bayer process residue solids takes place in highly caustic liquors, typically using high molecular weight polyacrylates. This represents an almost unique situation, and implies a totally different adsorption mechanism. Direct examination of polyacrylate adsorption within the complex matrix of real liquors and a mixture of residue phases is difficult, making it necessary to focus on a model substrate (hematite) and synthetic liquors (pH 13 at high ionic strength). Previous spectral studies have used ex situ techniques, with sample drying potentially altering the adsorbed species, leading to inconclusive results. This study presents for the first time direct in situ evidence of polyacrylate adsorption onto hematite obtained by Fourier Transform Infrared-Attenuated Total Reflection (FTIR-ATR) Spectroscopy. Adsorption and hence concentration of dilute polyacrylate solutions onto hematite-coated zinc selenide optics has provided spectra of adsorbed polymer under a range of conditions, unbiased by any contribution from the bulk polymer solution. Analysis of the polyacrylate carbon-oxygen stretching frequencies established differing modes of adsorption at low and high pH conditions. At pH 2 adsorption proceeded through bidentate chelation of the carboxylate to a surface ferric ion, facilitated through deprotonation of a carboxylic acid group and removal of a hematite surface hydroxyl group, i.e. chemisorption. Unshifted carboxyl peaks in the spectrum enabled the unadsorbed 'loops' and 'tails' to be distinguished from the adsorbed polymer, and represented at least 70% of the total polymer chain length.In contrast, at pH 13 adsorption of polyacrylate occurs via physisorption and was only possible with the addition of electrolyte. This adsorption was enhanced with increasing electrolyte concentrations up to 1 M NaCl. The hematite surface charge was negative at high pH, however with increasing ionic strength the specific adsorption of Na+ ions decreased the negative surface charge, and at very high salt concentrations the surface became positively charged. For electrolyte with different monovalent cations, polymer adsorption increased in the order Li+ > Na+ > Cs+. The identity of the monovalent cation had no effect on the polymer solution dimensions but the ability to reduce the magnitude of the hematite surface charge followed the same trend. This finding is consistent with the 'structure making - structure breaking' model proposed by Berube and de Bruyn. At both high and low pH, polyacrylate exhibited adsorption isotherms that are best described by the Langmuir expression. Surface coverage was greatest at low pH due to more available surface sites and the adsorbed polymer conformation (a greater fraction of loops and tails). Adsorbed conformation and hence maximum adsorption was independent of molecular weight at low pH, however at high pH maximum adsorption increased with increased molecular weight, indicating an adsorbed polymer configuration exhibiting a greater degree of loops and tails. While the individual carboxylate-surface interaction was stronger at low pH than high pH, both were relatively weak. Despite this, none of the polymers could be removed by washing, demonstrating the strength and irreversibility of the multi-attached polymer molecules.The stronger individual carboxylate-surface interactions at low pH is indicative of a higher activation energy of formation, and may be a contributing factor to the slower rate of adsorption at low pH. The rate of polyacrylate adsorption was dominated by mass transport limitations in all cases. The initial rate of adsorption was greater at lower polymer molecular weight, consistent with the relative polymer diffusion coefficients. This rate of adsorption was much less dependent on polymer molecular weight at high pH than at low pH, suggesting significantly different polymer-solvent interactions. It was clearly demonstrated that the sodium ion concentration within the high ionic strength Bayer liquors is more than sufficient to facilitate polyacrylate adsorption on bauxite residue. There is no need to postulate calcium bridging between the polymer and surface, as has been suggested in previous studies. Improved settling and clarity associated with the presence of calcium on residue surfaces is more likely due to enhanced particle coagulation prior to flocculation. FTIR-ATR has been shown to be an excellent tool for the in situ examination of polyacrylate adsorption onto hematite, and will be a powerful technique for the characterisation and subsequent comparison of the adsorption behaviour of other systems.